2018
DOI: 10.3390/su10114147
|View full text |Cite
|
Sign up to set email alerts
|

Do Urban Subway Openings Reduce PM2.5 Concentrations? Evidence from China

Abstract: With the fast-growing consumption of automobiles in China, vehicle fumes appear to be one of the major contributors to PM 2.5 (fine particles with a diameter of 2.5 µm or less) emissions. As a type of green transportation, Chinese urban subway transit has developed rapidly in recent years. This paper estimates the effect of urban subway openings on PM 2.5 concentrations in Chinese cities. Using daily air quality data for 29 Chinese cities from 2013 to 2018, and using regression discontinuity design, we find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Given the great potential for metropolitan subway systems to benefit urban communities, further growth in subway systems is anticipated. For example, studies in China have predicted opening new subway lines will decrease air pollution and provide substantial health benefits ( Lu et al. 2018 ; Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Given the great potential for metropolitan subway systems to benefit urban communities, further growth in subway systems is anticipated. For example, studies in China have predicted opening new subway lines will decrease air pollution and provide substantial health benefits ( Lu et al. 2018 ; Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…In metropolitan areas, subways have become an indispensable form of transport as they reduce traffic congestion and improve air quality by reducing emissions from gasoline and diesel engines [1]. Recently, Lu et al (2018) reported that adding new openings in the subway systems in Chinese cities between 2013 to 2017 reduced PM 2.5 concentrations by an average of 18 µg/m 3 and significantly improved air quality [2]. The Seoul Metropolitan subway is one of the largest metro traffic systems in the world.…”
Section: Introductionmentioning
confidence: 99%
“…We tested the substitution-of-driving effect by estimating both the short- and long-term effects of the subway openings on CO, which is a major pollutant emitted by motor vehicles. In 2016, the quantity of vehicle emissions in China was 44,725 million tons, of which 34.19 million tons were CO and 0.53 million tons were PM [ 53 ]. Therefore, we estimated the effect of the new subway openings on CO in order to test the alternatives to subway transit in the form of on-road transportation.…”
Section: Resultsmentioning
confidence: 99%